2019
DOI: 10.18483/ijsci.2068
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and Community Structure of Mormyridae (Pisces: Teleostei: Osteoglossiformes) from Niger River in Northern Benin: Threats, Conservation and Valorization Perspectives

Abstract: Mormyrid fishes are of great commercial and economic importance in the artisanal fisheries of the Niger River in Benin. We investigated species composition and community structure of this taxa in order to contribute to species management and sustainable exploitation. Mormyrid individuals were collected monthly from February 2015 to July 2016 using cast nets, gill nets and seines. Among a total of 6825 individuals collected, eleven (11) species belonging to 9 genera were inventoried. Numerically, Marcusenius se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In addition, is a fish species that is active during the night and typically found near the bottom of the water column that sustains its diet by consuming invertebrates, detritus, and plant fragments, documented by Omotosho (1993) [35] . According to Kayode et al, (2019) [24] Mormyrid fishes have been identified as having considerable commercial and economic significance in the artisanal fisheries of the Niger River in Benin. They are found in fast moving (lotic) freshwaters of tropical Africa (Fletcher and Crawford, 2001) [20] while Fawole (2002) [19] ; Lauren and Jason (2021) [26] ; and Samuel et al, (2022) [42] reported they are typically found in shallow, slow moving (lentic) water habitats and are spawn more or less throughout the year reported by Scott (1974) [43] and confirmed by Fawole (2002) [19] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, is a fish species that is active during the night and typically found near the bottom of the water column that sustains its diet by consuming invertebrates, detritus, and plant fragments, documented by Omotosho (1993) [35] . According to Kayode et al, (2019) [24] Mormyrid fishes have been identified as having considerable commercial and economic significance in the artisanal fisheries of the Niger River in Benin. They are found in fast moving (lotic) freshwaters of tropical Africa (Fletcher and Crawford, 2001) [20] while Fawole (2002) [19] ; Lauren and Jason (2021) [26] ; and Samuel et al, (2022) [42] reported they are typically found in shallow, slow moving (lentic) water habitats and are spawn more or less throughout the year reported by Scott (1974) [43] and confirmed by Fawole (2002) [19] .…”
Section: Introductionmentioning
confidence: 99%